P103 Aberrant DNA damage response of B cell populations in systemic lupus erythematosus. (23rd March 2020) - Manolakou, Theodora; Banos, Aggelos; Filia, Anastasia; Pieta, Antigone; Verginis, Panayotis; Boumpas, Dimitrios
Abstract : Background: SLE patients demonstrate increased levels of DNA damage, defective DNA repair and polymorphisms in genes required for maintaining genomic stability. Effective DNA damage response is crucial for the generation of antibodies by B cells while excessive production of autoantibodies is a universal feature of the disease. We sought to investigate DNA damage response/repair a) in total B cells and their subtypes in several tissues of a murine SLE model and b) in transcriptomic data derived by B cell subtypes from the peripheral blood of SLE patients. Methods: Flow Cytometry analysis was performed for total B cells or their subtypes combined with γH2ΑX DNA damage marker in blood, spleen, lymph nodes and bone marrow (BM) of NZBW/F1 murine SLE model (pre-diseased, n=5/diseased, n=4) and in the blood of SLE patients (n=7) compared to healthy controls (HC, n=9). Gene set enrichment analysis (GSEA) was performed in a published B cell populations transcriptomic dataset 1 derived from the blood of SLE patients (n=9) compared to HC (n=12). Results: Increased γH2ΑX expression was identified in B cells from blood and BM of diseased mice compared to pre-diseased (p=0.02) as well as from blood of SLE patients with high disease activity compared to HC (p=0.02). Deregulated γH2ΑX expression levels were detected in distinct B subtypes of diseased mice (p<0.05). GSEA showed significant enrichment of DNA damage response/repair pathways in B subtypes from the blood of SLE patients compared to HC (table 1 ). Conclusions: NZBW/F1 murine SLE model presents with increased DNA damage in blood- and BM-derived total B cells and subtypes. Peripheral B cells and distinct B subpopulations show aberrant DNA damage response and repair in SLE patients. Acknowledgements: ERC (No. 742390). Reference: Scharer, Christopher D., et al. 'Epigenetic programming underpins B cell dysfunction in human SLE.' Nature immunology 2019; 20.8; 1071–1082.